2019
DOI: 10.11628/ksppe.2019.22.6.677
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Visit Characteristics in Neighborhood Forest on Individual Life Satisfaction

Abstract: Recently, the importance and effectiveness of neighborhood forests have been increasing in relation to the quality of life of urban residents. However, there are very few domestic studies that analyzed the correlation between visit characteristics and life satisfaction. Therefore, the study aims to understand how people use the forest for recreation and determine how visit characteristics in neighborhood forests affect individual life satisfaction(ILS). A nationwide survey (N=2,624) was conducted on visit freq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Second, the measurement of explanatory variables may be inappropriate. The intensity of forest-related activities was found to correlate with the general SWB or the evaluation of forest spaces for recreational purposes [29,31]. The current models assess the levels of forest-related activities as yes-or-no experiences during the past year.…”
Section: Possibilities and Challenges For Forest Swbmentioning
confidence: 93%
See 1 more Smart Citation
“…Second, the measurement of explanatory variables may be inappropriate. The intensity of forest-related activities was found to correlate with the general SWB or the evaluation of forest spaces for recreational purposes [29,31]. The current models assess the levels of forest-related activities as yes-or-no experiences during the past year.…”
Section: Possibilities and Challenges For Forest Swbmentioning
confidence: 93%
“…Several studies have further explored the impact of interactions, not only physical closeness, with nature on SWB. Jang et al reported that the frequency of forest visits is more relevant to SWB than the distance to urban forests in South Korea [29]. It was found in Italy and the UK that longer and more frequent visits to urban green spaces improved the perceived benefits and well-being of respondents [30].…”
Section: Natural Capitalmentioning
confidence: 99%
“…Future heritage policies should investigate the impact of cultural landscapes on visitors' behavior to improve the quality of people's lives (Jang et al, 2019;Stegmeijer et al, 2021;United Nations, 2020). The negative influence of the COVID-19 pandemic on people's mental health and quality of life should also be considered (Ban, 2021;Choi, 2021;Lee, 2020).…”
Section: According To the 2018 South Korean Cultural Heritagementioning
confidence: 99%
“…Hong et al (2020) also suggest that place attachment is developed through a continuous process of interaction between visitors and all the inherent attributes of a place, as well as the external elements. Therefore, visitors' experiences and understanding of a site's importance are related to generating a psychological impact and place attachment (Jang et al, 2019;Kim and Miller, 2019).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation